Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2024
DOI: 10.1001/jamanetworkopen.2024.6589
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation for Anxiety During Laparoscopic Colorectal Cancer Surgery

Chunyan Li,
Mingshu Tao,
Dexian Chen
et al.

Abstract: ImportancePerioperative anxiety is prevalent among patients undergoing surgical treatment of cancer and often influences their prognosis. Transcranial direct current stimulation (tDCS) has shown potential in the treatment of various anxiety-related disorders, but data on the impact of tDCS on perioperative anxiety are limited.ObjectiveTo evaluate the effect of tDCS in reducing perioperative anxiety among patients undergoing laparoscopic colorectal cancer (CRC) resection.Design, Setting, And ParticipantsThis ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Animal models have demonstrated tDCS can quicken emergence and recovery from volatile anesthesia, indicating potential perioperative utility ( 27 , 32 ). Most recently, a clinical study demonstrated reduced anxiety in patients who received tDCS in the 24 hours prior to surgery ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Animal models have demonstrated tDCS can quicken emergence and recovery from volatile anesthesia, indicating potential perioperative utility ( 27 , 32 ). Most recently, a clinical study demonstrated reduced anxiety in patients who received tDCS in the 24 hours prior to surgery ( 33 ).…”
Section: Introductionmentioning
confidence: 99%